THE ANALYSIS OF CREDIT ALLOCATION ITS INFLUENCE TO PROFIT AT BINA USAHA COOPERATION BERSAMA KUD BANDUNG - Lia Yulianti; Herien Douglas (JURISMA : Jurnal Riset Bisnis & Manajemen, 2015)
The Bina Usaha Bersama cooprative of  KUD Bandung foundation is the committee running the credit-giving service. Credit-giving service operated by this cooperative is very important for the members because they can improve  their prosperous life by this service. Credit facility given by this cooperative not only for helping it’s members, but also for gaining the desired profit called as Surat Hasil Usaha (SHU). SHU is cooperative income received in one year book decreased by cost, reduction, and another obligationThe aim of the study is to examine developments in credit Bina Usaha Bersama of KUD Bandung foundation from 2003 to 2008, to determine earning growth in Bina Usaha Bersama of KUD Bandung foundation from 2003 to 2008, and to determine the effect on profits in Bina Usaha Bersama of KUD Bandung foundation from 2003 to 2008.The methods used in this research are descriptive method and verificative method with quantitative approach. The data type used is secondary data. Whereas analysis method and hypothesis planning used is simple linier regression analysis, Pearson correlative regression analysis, determinasion coefisien, and hypothesis testBased on research, the result from simple linier regression analysis calculation is Y = 5,23 + 0,098 X, it means that regression coefisien is one direction (positive). While the result from Pearson  correlation calculation is 0,385, it means that the correlation between two variables is low an positive (one direction). The result from determination coefisien calculation is 15,603%, it means that credit-giving can influences the profit about 15,603%, an the remain 84,397% influences by other factors which is not studied by the writter, such as cash, or credit stock and reduction. The result from hypothesis test is value of thitung about 0,860 and value of ttabel about 2,776, it means that between credit-giving and profit in Bina Usaha Bersama Cooperative of KUD Bandung Foundation no have significant influence.